Psychological Traits of Patients with Central Serous Chorioretinopathy (Literature Review) - V. A. Shaimova; T. G. Kravchenko; G. M. Arslanov; T. B. Shaimov; R. B. Shaimov (Oftalʹmologiâ, 2023)
Central serous chorioretinopathy (CSC) is a polyethological disease. CSC is one of the few eye diseases for which the relationship between the occurrence, course of the disease and patient psychosocial characteristics has been demonstrated including personality traits and the level of external stress factors. Excessive stimulation such as stressful living conditions, exogenous factors and personal predisposition can lead to CSH. The disease often occurs against the background of acute or chronic stress. Patients with central serous chorioretinopathy are characterized by certain personality traits i.e., type A personality, including a tendency to overachievement, competition, perfectionism, and a sthenic desire to maintain professional status. At the same time, insomnia and sleep apnea, depressive and anxiety states, post-traumatic stress disorder and alexithymia, high blood pressure, Helicobacter pylori, autoimmune diseases, psychopharmacological medication, hormone therapy are among the risk factors.